2000
DOI: 10.1023/a:1005142429725
|View full text |Cite
|
Sign up to set email alerts
|

Normative Influences on Aggression in Urban Elementary School Classrooms

Abstract: We report a study aimed at understanding the effects of classroom normative influences on individual aggressive behavior, using samples of 614 and 427 urban elementary school children. Participants were assessed with measures of aggressive behavior and normative beliefs about aggression. We tested hypotheses related to the effects of personal normative beliefs, descriptive classroom norms (the central tendency of classmates' aggressive behavior), injunctive classroom normative beliefs (classmates' beliefs abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
353
3
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(390 citation statements)
references
References 21 publications
26
353
3
8
Order By: Relevance
“…A second goal of Study 2 was to investigate whether the observed effect of trait-relevant information in Study 1 would still be obtained if yet another assessment of approval of aggression were used. To that end, children in Study 2 were simply asked if it would be "okay" to hit the story character, a methodology that has been used frequently in studies of children's endorsement of aggression [Henry et al, 2000;Huesmann and Guerra, 1997;Giles and Heyman, 2003]. …”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A second goal of Study 2 was to investigate whether the observed effect of trait-relevant information in Study 1 would still be obtained if yet another assessment of approval of aggression were used. To that end, children in Study 2 were simply asked if it would be "okay" to hit the story character, a methodology that has been used frequently in studies of children's endorsement of aggression [Henry et al, 2000;Huesmann and Guerra, 1997;Giles and Heyman, 2003]. …”
Section: Studymentioning
confidence: 99%
“…One aspect of children's social cognition that has been of interest to researchers attempting to understand aggression in childhood is the extent to which children endorse, or approve of, the use of aggression as a means of responding to the provocations of others [Coie and Dodge, 1998;Giles and Heyman, 2003;Huesmann and Guerra, 1997;Henry et al, 2000; see also Erdley and Asher, 1998]. The tendency to endorse aggression has been linked to several negative behavioral outcomes, including increased levels of aggressiveness [Erdley and Asher, 1998;Huesmann and Guerra, 1997;Guerra and Slaby, 1989;Gouze, 1987], deficits in prosocial behavior [Erdley and Asher, 1998] 1985;Perry et al, 1986].…”
Section: Introductionmentioning
confidence: 99%
“…Social norms can be injunctive (indicating approval of a behavior, or what persons ought to do) or descriptive (indicating prevalence of a behavior, or what most persons actually do). 31 Empirical studies focused on behaviors such as speeding, 32 recycling, 31 smoking, 33 and classroom aggression 34 suggest that both types of perceived norms might have roles in shaping beliefs and behaviors. Importantly, such subjective assessments of the social environment might be just as or even more important than objective assessments in shaping parenting.…”
Section: Introductionmentioning
confidence: 99%
“…Depois de controlados do factores demográficos, tipo de educação (isto é, educação especial) e a percepção dos participantes relativamente ao abusos de substâncias por parte dos seus pais e pares, as normas da escola foram significativamente correlacionadas com o consumo de substâncias por parte dos participantes em ambas as classes de substâncias. Henry et al (2000) analisaram a associação entre as normas explicativas e as normas imperativas e a agressão no comportamento individual entre 614 estudantes do 1.º ciclo de diversas etnias, em 45 turmas de 14 escolas urbanas e suburbanas com problemas económicos (e posteriormente replicaram os resultados em estudantes de 21 turmas em 16 escolas). Não encontraram efeitos resultantes das normas explicativas (comportamentos agressivos dos outros na turma, tal como registado pelos professores).…”
Section: Normasunclassified
“…Os indivíduos podem apresentar as suas próprias atitudes e valores, e estes podem ser agregados para se conceber as normas comuns naquele contexto (Henry et al, 2000), ou em características do próprio contexto em si. As escalas de clima social desenvolvidas por Moss e col.…”
Section: Medidas De Análise Compostas Assentes Emunclassified